Carotid Cavernous Fistula: Role of Open Surgery in The Era of Endovascular Treatment - Sharma, Rajau K; Sharma, Gopal R; Bista, Prakash; Jha, Rajiv (Nepal Journal of Neuroscience, 2017)
A 18-year-old right handed girl presented with progressive proptosis, chemosis, diplopia and an orbital bruit of right eye, 3 days after alleged history of fall from a tree, The intraocular pressure was increased. The suspected diagnosis of a direct carotid cavernous fistula (CCF) was confirmed by CT angiography CT Angiography showed direct fistulous communication of cavernous segment of right internal carotid artery with right cavernous sinus (type A right CCF) and linear minimally displaced fracture of right zygomatic arch and linear undisplaced fracture of wall of right orbit. The patient underwent right pterional craniotomy and transcavernous occlusion of fistula of right internal carotid artery (ICA). Surgery was performed with gradual resolution of the symptoms and normalization of the intraocular pressure. The pathogencsis, symptomatology, treatment of carotid cavernous fistulas are discussed. Nepal Journal of Neuroscience, Volume 14, Number 1, 2017, Page: 36-39